Pension System Viability and Reform Alternatives in the Czech Republic - Laursen, Thomas (Washington, D.C. : International Monetary Fund, 2000)
The finances of the Czech pension system have deteriorated markedly in recent years and the aging population will add further strains in the future. The system is also burdened by significant distortions and disincentive effects. This paper assesses the current pay-as-you-go (PAYG) system, including its long-run viability, and discusses reform options. It concludes that alterations to the basic PAYG parameters can go a long way toward addressing the problems, although more systemic changes-such as pre-funding, strengthening the link between contributions and benefits, and diverting part of the pension contributions to a mandatory, private pension savings pillar-could also help.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet